EFEKTIVITAS PEMBELAJARAN MATA PELAJARAN EKONOMI MELALUI IMPLEMENTASI METODE COOPERATIVE LEARNING BERBASIS KASUS DAN PEMBIASAAN LITERASI PADA KELAS XI IIS DI MA SUNAN AMPEL PLOSOKLATEN TAHUN PELAJARAN 2019/2020 - Lianawati, Dian; Sugiono, Sugiono (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The purpose of this study was to determine the relationship between the implementation of case-based cooperative learning methods and literacy habituation on the effectiveness of learning. This research is a quantitative research. The subject of the research was 30 students of class XI IIS MA Sunan Ampel Plosoklaten. The data collection techniques used observation sheets, questionnaires, interviews, and documentation. Techniques for data analysis are quantitative descriptive analysis techniques. The results showed that: (1) the implementation of case-based cooperative learning had a significant positive effect on the effectiveness of learning as seen from the significance value of 0.002 < 0.05 and the tvalue of 3.417 > ttable 2.052 with an error rate of 5% (α = 0.05), (2) literacy habituation has no significant effect on the effectiveness of learning which can be seen from the significance value of 0.159 > 0.05 and the tvalue of 1.447 < ttable 2.052, (3) the implementation of case-based cooperative learning and literacy habituation simultaneously has a significant positive effect on effectiveness learning indicated by a significance value of 0.00 < 0.05 and tvalue 23.579 > ttable 3.354, (4) the calculation of the determinant coefficient shows that 60.9% of the effectiveness of learning is influenced by the case-based cooperative learning method and literacy habituation, the rest is influenced by other factors